A non-mammalian Toll-like receptor 26 (TLR26)gene mediates innate immune responses in yellow catfish Pelteobagrus fulvidraco. Issue 95 (December 2019) - Liu, Qiu-Ning; Yang, Ting-Ting; Wang, Cheng; Jiang, Sen-Hao; Zhang, Dai-Zhen; Tang, Bo-Ping; Ge, Bao-Ming; Wang, Jia-Lian; Wang, Dong; Dai, Li-Shang
Abstract: In this study, we identified a fish-specific Toll-like receptor (TLR) in Pelteobagrus fulvidraco, an economically important freshwater fish in China. This TLR, Pf TLR26, was shown to be encoded by a 3084 bp open reading frame (ORF), producing a polypeptide 1027 amino acids in length. The Pf TLR26 protein contains a signal peptide, eight leucine-rich repeat (LRR) domains, two LRR_TYP domains in the extracellular region, and a Toll/interleukin (IL)-1 receptor (TIR) domain in the cytoplasmic region, consistent with the characteristic TLR domain architecture. This predicted 117.1 kDa protein was highly homologous to those of other fish, with phylogenetic analysis revealing the closest relation to TLR26 of Ictalurus punctatus . Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis showed that the Pf TLR26 gene was expressed in all tissues tested, with the highest expression levels seen in the head kidney and blood, and the lowest seen in muscle. Pf TLR26 exhibited significant upregulation in liver, spleen, head kidney, and blood at different time points following challenge with the common TLR agonists lipopolysaccharide (LPS) and polyriboinosinic polyribocytidylic acid (Poly I:C). Taken together, these results suggest that Pf TLR26 may be an important component of the P. fulvidraco innate immune system, participating in the transduction of TLR signaling under pathogen stimulation. Highlights: A TLR26 gene was cloned from yellow catfish Pelteobagrus fulvidraco. TLR26 mRNA levels were detected in a wide range of P. fulvidraco tissues. The mRNA expression levels of PfTLR26 were up-regulated in response to Poly I:C or LPS challenge.